Comparison of Postnatal Growth Charts of Singleton Preterm and Term Infants Using World Health Organization Standards at 40–160 Weeks Postmenstrual Age: A Chinese Single-Center Retrospective Cohort Study - Zhang, Li; Lin, Jian-Gong; Liang, Shuang; Sun, Jin; Gao, Nan-Nan; Wu, Qiong; Zhang, Hui-Yun; Liu, Hui-Juan; Cheng, Xiang-Deng; Cao, Yuan; Li, Yan (Frontiers in Pediatrics, 2021)
There remains controversy regarding whether the growth charts constructed from data of term infants such as World Health Organization (WHO) standards can appropriately evaluate the postnatal growth of preterm infants. This retrospective cohort study conducted in the First Affiliated Hospital of Shandong First Medical University in Jinan China, aimed to compare the postnatal growth charts of singleton preterm, term infants and the WHO standards at 40–160 weeks postmenstrual age (PMA). . 5459 and 15185 sets of longitudinal measurements (length/height, weight, head circumference [HC] and body mass index [BMI]) from birth to 160 weeks PMA, were used to construct growth charts for 559 sinelton preterm (mean PMA at birth, 33.84 weeks) and 1596 sinelton term infants (born at 40 weeks PMA), respectively, using Generalized Additive Models for Location, Scale, and Shape (GAMLSS) method. Z-scores (prematurity corrected) were calculated using WHO Anthro software. Compared to the WHO standards, all parameters of preterm infants were larger, especially length/height and weight; the gap between the two almost spanned two adjacent centile curves. Compared to term controls, length/height, weight, and BMI of preterm infants were higher at 40 weeks PMA, surpassed by term infants at 52–64 weeks PMA, and quite consistent thereafter; HC of preterm infants at 40–160 weeks PMA was quite consistent with both term controls and the WHO standards. The Z-scores for length/height, weight, and BMI of preterm infants relative to the WHO standards gradually decreased from 1.20, 1.13, and 0.74 at 40–44 weeks PMA to 0.67, 0.42, and 0.03 at 132–160 weeks PMA, respectively; Z-scores for HC of preterm infants rapidly decreased from 0.73 to 0.29 at 40–50 weeks PMA, and then fluctuated in the range of 0.08–0.23 at 50–160 weeks PMA. Preterm infants had higher growth trajectories than the WHO standards and similar but not identical trajectories to term infants during the first 2 years of life. These findings reemphasize the necessity of constructing local growth charts for Chinese singleton preterm infants.